Arecoline stimulated early growth response‐1 production in human buccal fibroblasts: Suppression by epigallocatechin‐3‐gallate. Issue 4 (3rd April 2014) - Hsieh, Yu‐Ping; Chen, Hsin‐Ming; Chang, Jenny Zwei‐Chieng; Chiang, Chun‐Pin; Deng, Yi‐Ting; Kuo, Mark Yen‐Ping
Abstract: Background: Early growth response‐1 (Egr‐1) protein plays an important role in many human fibrotic diseases. Areca nut chewing is the most important risk factor of oral submucous fibrosis (OSF). Methods: Egr‐1 protein expression in OSF was examined using antibody to Egr‐1. Arecoline‐induced Egr‐1 expression and its signaling pathways were assessed by Western blot analyses in human buccal mucosal fibroblasts (BMFs). Results: Elevated Egr‐1 staining was observed in epithelial cells, fibroblast, and inflammatory cells in 7 of 10 OSF cases. Arecoline, a main alkaloid found in the areca nut, stimulated Egr‐1 synthesis in BMFs. Pretreatment with antioxidant N‐acetyl‐L‐cysteine, c‐Jun NH2‐terminal kinase inhibitor SP600125, and extracellular signal‐regulated kinase inhibitor PD98059 significantly reduced arecoline‐induced Egr‐1 synthesis. Epigallocatechin‐3‐gallate (EGCG) inhibited arecoline‐induced Egr‐1 synthesis and collagen gel contraction in a dose‐responsive manner. Conclusion: Constitutive Egr‐1 expression during areca nut chewing may play a role in the pathogenesis of OSF. EGCG could be a good candidate for prevention or treatment of OSF. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 493–497, 2015